Withaferin A protects against palmitic acid-induced endothelial insulin resistance and dysfunction through suppression of oxidative stress and inflammation - Batumalaie, K.; Amin, M.A.; Murugan, D.D.; Sattar, M.Z.A.; Abdullah, N.A. (Nature Publishing Group, 2016)
Activation of inflammatory pathways via reactive oxygen species (ROS) by free fatty acids (FFA) in obesity gives rise to insulin resistance and endothelial dysfunction. Withaferin A (WA), possesses both antioxidant and anti-inflammatory properties and therefore would be a good strategy to suppress palmitic acid (PA)-induced oxidative stress and inflammation and hence, insulin resistance and dysfunction in the endothelium. Effect of WA on PA-induced insulin resistance in human umbilical vein endothelial cells (HUVECs) was determined by evaluating insulin signaling mechanisms whilst effect of this drug on PA-induced endothelial dysfunction was determined in acetylcholine-mediated relaxation in isolated rat aortic preparations. WA significantly inhibited ROS production and inflammation induced by PA. Furthermore, WA significantly decreased TNF-α and IL-6 production in endothelial cells by specifically suppressing IKKβ/NF-κβ phosphorylation. WA inhibited inflammation-stimulated IRS-1 serine phosphorylation and improved the impaired insulin PI3-K signaling, and restored the decreased nitric oxide (NO) production triggered by PA. WA also decreased endothelin-1 and plasminogen activator inhibitor type-1 levels, and restored the impaired endothelium-mediated vasodilation in isolated aortic preparations. These findings suggest that WA inhibited both ROS production and inflammation to restore impaired insulin resistance in cultured endothelial cells and improve endothelial dysfunction in rat aortic rings.